Optimizing the mixture design of polymer concrete: An experimental investigation. (10th April 2018) - Jafari, Khashayar; Tabatabaeian, Mojtaba; Joshaghani, Alireza; Ozbakkaloglu, Togay
Highlights: Polymer concrete (PC) mixes were studies using destructive and non-destructive testing methods. The optimum mix design of PC was determined using Taguchi and ANOVA methods. The temperature during testing was found to be the most influential parameter affecting the destructive test results. Predictive models were proposed to determine the splitting tensile and flexural strengths of PC. Abstract: Over the last few decades, polymer concrete (PC) has been finding use in quick repairing of concrete structures. However, there have been only few studies on the mechanical behavior of PC. The aim of this study is to evaluate the mechanical behavior of PC using destructive and non-destructive tests (NDT). The mixtures were prepared with three different polymer ratios (10%, 12%, and 14%) and two different coarse aggregate sizes (4.75–9.5 mm and 9.5–19 mm). The samples were subsequently tested under three different temperatures (−15 °C, +25 °C, and +65 °C). The Taguchi method and analysis of variance (ANOVA) were used to optimize PC mixes based on the compressive, splitting-tensile, and flexural strengths under varying polymer content, coarse aggregate size, and temperature. NDTs, including ultrasonic pulse velocity and electrical resistivity tests, were carried out to gain insights into the porosity and void content of the specimens. Scanning electron microscopy (SEM) was used to analyze the bonding interface between aggregates and polymer, microstructure phase, and pores that were present in the structure of the PC. Results show that a decrease in the temperature from +25 °C to −15 °C led to an improvement in the mechanical properties of PC mixes, whereas an increase in the temperature from +25 °C to +65 °C adversely affected the mechanical properties. Based on NDT, it was found that increasing the coarse aggregate size and polymer ratio reduced the porosity of specimens. This is attributed to the decreased surface area to volume ratio with increasing particle size, which allowed the polymer to completely coat the surface of aggregates. Finally, a set of expressions was proposed to predict the mechanical properties of PC.